PENGEMBANGAN UKM TUMPENG MELALUI DIGITALISASI TEKNOLOGI DAN MANAJEMEN USAHA DI BANJAR KEMENUH INDUK DESA KEMENUH KECAMATAN SUKAWATI KABUPATEN GIANYAR - Anak Agung Media Martadiani; I Ketut Darma; Ida Bagus Komang Suarka (Jurnal Lentera Widya, 2022)
The MSME sector is expected to be able to become a new source of strength for the national economy in facing the crisis. To become a new force in the economic field, the government pays attention to human resources and management. Innovation from the average MSME so far is still minimal so that SME businesses often run in place. Not to mention the financial or business capital problems that often hinder SMEs from increasing their productivity. The last issue that must be considered is the limited access to marketing. One of the villages targeted for PKM activities is Tumpeng UKM. The location of this PKM Partner is at Br. Kemenuh Parent, Kemenuh Village, Sukawati, Gianyar, which is ±18 km from the Warmadewa University campus. According to Mrs. Ni Kadek Rupi, the impact felt by partners during the current pandemic is the obstacle in marketing due to the decline in sales. The problem faced by partners is that it is difficult to develop a business. Due to limited sources of capital, lack of promotion, not yet keeping records related to the costs incurred and carried out in running the running partner as a whole. The purpose of this service is to provide solutions to increase sales during the pandemic, therefore the service team provides solutions in the form of providing financial management services, and marketing management and entrepreneurial governance.